SOCIO - PSYCHOLOGICAL CONTEXT OF RELATIVES OF SUICIDES: AN ANALYSIS OF AFFECTIVITY AND COPING STRATEGIES (Fiep Bulletin - online, 2012)
Suicide is an individual activity to extinguish life itself. This fact occurs since man became aware to exist as thinking being and owner of his actions. The referred study aimed to analyze the socio-psychological context of suicides' relatives, the analysis of affectivity and coping strategies. To this end, 20 families took part and responded to a semi-structured questionnaire. The main results indicated the characterization of the family members, aging between 27 and 37 years, women with primary education, married, Catholic and regarding religious practice (40%) consider themselves average practitioners of religion. Regarding the economic aspect, the family income is around 1-3 minimum wages, retirees, with large household composition, and own their own homes. However, they don't vehicles. Suicide is an issue of social relevance, a public health issue which suggests the necessity of development of preventive measures and the study points out elements for early assessment and intervention in risk situations. The study highlights the importance of analyzing affectivity and coping strategies of family members seeking to better understand the underlying reasons for their actions, since the stressful situations favor the appearance of emotional reactions essential for the survival of man. Increased efforts are required to sensitize the population about the risks prominent to suicide. Therefore, the public administration should ensure rapid access to psychiatric support, through the primary health care in cases of high risk for suicide Public policies should encourage and implement appropriate training and professional support for programs that have the goal of preventing suicide.
Keywords: Affectivity; Coping Strategies; Suicide.